PENGARUH BANTUAN DANA USAHA PRODUKTIF TERHADAP PENDAPATAN NELAYAN DI DESA SUNGAI LIMAU KABUPATEN MEMPAWAH - Putri, Dea Kamalia; Asriati, Nuraini; Parijo, Parijo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know the influence of productive business funds towards the fishermen?s income in Sungai Limau Village Sungai Kunyit District Of mempawah.  The method in this research is the descriptive. This is a  correlational research. The number of samples in this research is 60 fishermen. The sampling technique in this research is saturation sampling. Data collection techniques in this research are direct communication techniques (interview guidelines), indirect communication techniques (questionnaire), and documentary techniques (documentations). The results of this research showed that (1) the percentage of productive business funds variable  in Sungai Limau Village Sungai Kunyit District Of mempawah is 71.67% in medium category with the interval 44,57% ? X <50,49%, (2) the percentage of the fishermen?s income variable is 66,66% in medium category with the interval 21,31% ? X <26,65%,(3) t count 4,986> t table 2,002 so that Ho rejected and Ha is accepted then there is significant influence of productive business fund for fishermen?s income in Sungai Limau Village Sungai Kunyit District Of mempawah for 30%. Keywords: Funds, Productive Business, Fishermen?s Income